Dry needling in triceps surae muscles and its influence on pressure pain threshold and lower limb posture in active elderly women: a randomized, blinded controlled clinical trial - Martins, Camila Morábito; Ferreira, Fernando Borges; Tozim, Beatriz Mendes; Barbosa, Pedro Marco Kazan (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Aging leads to the loss of anatomical structures and physiological processes such as postural stability. Poor postural control leads to a shift in the center of gravity, thus overloading the musculature. Muscles overloaded due to postural changes do not show enough muscle contraction, causing the appearance of trigger points (TP). Among the PG deactivation methods, the Dry Needling (DN) has been shown to be a good response method in clinical practice. Objective: To analyze the immediate effect of DN on pressure pain threshold (PPT) of latent trigger points of the sural triceps muscles, in order to verify whether there is improvement in the posture of the lower limbs of active elderly women. Methods: A randomized, controlled and blind clinical trial (patients) was carried out. The sample consisted of physically active elderly women from the community. Divided into two groups: DN Group (DNG) and Control Group (CG). Both groups underwent an initial assessment, treatment (DNG) or sham (CG), and reassessment. The tests were: pressure algometer and biophotogrammetry. Data were analyzed from Normality using the Shapiro-Wilk test. The characterization of the sample was analyzed by multivariate analysis of variance (MANOVA) for comparison between groups. For inter and intragroup analysis, mixed Anova with post hoc Bonferroni was used. The level of significance used was p<0.05. Results: The PPT showed an increase in the intragroup analysis for the right (14.03%) and left (14.92%) sides in the GDN group, as for the intergroup analysis, the results of the reassessment were higher in the DNG group compared to the GC. Regarding the posture of the lower limbs, there was no significant improvement in the intergroup and intragroup analyses. Conclusion: The present study demonstrated that the application of Dry Needling in PG in the sural triceps musculature presents an increase in the pressure pain threshold, however, only one session of the technique application was not enough to present a significant improvement in the posture of the lower limbs. of active elderly women. Search registered on the ReBEC (Brazilian Registry of Clinical Trials) platform under the number RBR-97sqsb.